Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting

Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting